Contrasting patterns of sexually selected traits in Mediterranean and continental populations of European mouflon. Issue 4 (24th January 2020) - Kavčić, Krešimir; Corlatti, Luca; Safner, Toni; Budak, Nikola; Šprem, Nikica
Abstract: The expression of sexually selected traits in highly dimorphic ungulates may be influenced by environmental quality. Variations in habitat conditions can impose different constraints on the allocation of energy resources to male life‐history traits, and possibly alter the female preferences for specific features. Here, we compared the horn growth patterns in male European mouflon Ovis aries musimon living in different habitats (Mediterranean vs. continental) but sharing a common genetic origin. We hypothesized that the expression of sexually selected traits such as horn development should be promoted in more favorable habitat conditions (i.e., Mediterranean). Using linear mixed models on data retrieved from individuals harvested under the same hunting regime, we found longer horns and greater individual variance in horn segment length in the Mediterranean population than in the continental one. Furthermore, Mediterranean rams showed no evidence of compensatory horn growth, as opposed to the continental rams. Unexpectedly, horn base circumference was greater in the continental habitat than in the Mediterranean one. The overall results suggest different patterns of investment in horns in the two populations, with seemingly stronger pressure and consequences of sexual selection on mouflon rams living in more favorable environments. Although the role of hunters' selectivity cannot be excluded a priori, our data suggest that the differences in the expression of sexually selected traits in our study populations may be influenced by environmental conditions. Because sexual selection can impose substantial fitness costs on individuals, further investigations on the trade‐offs between reproduction and survival would improve our understanding of the dynamics of mouflon populations living in different environmental conditions. Abstract : The expression of sexually selected traits in highly dimorphic ungulates may be influenced by environmental quality. We compared the horn growth patterns in male European mouflon living in different habitats but sharing a common genetic origin. Our results suggest different patterns of investment in horns in two populations, suggesting that the differences in the expression of sexually selected traits may be influenced by environmental conditions.